Table of integrals, series, and products - Gradshte?in, I. S. (Academic Press, 2000)
The Table of Integrals, Series, and Products is the major reference source for integrals in the English language. It is essential for mathematicians, scientists, and engineers, who rely on it when identifying and subsequently solving extremely complex problems. The Sixth Edition is a corrected and expanded version of the previous edition. It was completely reset in order to add more material and to enhance the visual appearance of the information. To preserve compatibility with the previous edition, the original numbering system for entries has been retained. New entries and sections have been inserted in a manner consistent with the original scheme. Whenever possible, new entries and corrections have been checked by means of symbolic computation. -Completely reset edition of Gradshteyn and Ryzhik reference book -New entries and sections kept in orginal numbering system with an expanded bibliography -Enlargement of material on orthogonal polynomials, theta functions, Laplace and Fourier transform pairs and much more.